2021
DOI: 10.1186/s12875-021-01451-7
|View full text |Cite
|
Sign up to set email alerts
|

A mixed methods study on medicines information needs and challenges in New Zealand general practice

Abstract: Background Medicines are central to healthcare in aging populations with chronic multi-morbidity. Their safe and effective use relies on a large and constantly increasing knowledge base. Despite the current era of unprecedented access to information, there is evidence that unmet information needs remain an issue in clinical practice. Unmet medicines information needs may contribute to sub-optimal use of medicines and patient harm. Little is known about medicines information needs in the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Additionally, younger doctors were easier to access and were more cooperative to participate in this study. Several studies note that a lack of time (Sharma et al, 2017;Campbell et al, 2021;Zielińska and Hermanowski, 2022) and limited access to credible drug information sources (Tumwikirize et al, 2008;Sharma et al, 2017;Zielińska and Hermanowski, 2022) are the main obstacles when searching for drug information; approximately a quarter of the physicians in this study reported that time constraints are a challenge. The most frequent challenges encountered concerned the vast number of available sources, knowing which sources are trusted and credible, and an inability to access subscription-only journals and websites, although these issues were less problematic for physicians who work, or have worked, in academia (p < 0.001).…”
Section: Discussionmentioning
confidence: 70%
“…Additionally, younger doctors were easier to access and were more cooperative to participate in this study. Several studies note that a lack of time (Sharma et al, 2017;Campbell et al, 2021;Zielińska and Hermanowski, 2022) and limited access to credible drug information sources (Tumwikirize et al, 2008;Sharma et al, 2017;Zielińska and Hermanowski, 2022) are the main obstacles when searching for drug information; approximately a quarter of the physicians in this study reported that time constraints are a challenge. The most frequent challenges encountered concerned the vast number of available sources, knowing which sources are trusted and credible, and an inability to access subscription-only journals and websites, although these issues were less problematic for physicians who work, or have worked, in academia (p < 0.001).…”
Section: Discussionmentioning
confidence: 70%
“…Usually, they are required to carefully examine the drug information to consider the possibility of the culprit drugs. However, time constraints for medical practitioners in clinical settings pose a challenge in seeking drug information on each prescribed drug 32–34 . The ranking of drugs proposes a priority order to examine, leading to time‐saving for medical practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…However, time constraints for medical practitioners in clinical settings pose a challenge in seeking drug information on each prescribed drug. [32][33][34] The ranking of drugs proposes a priority order to examine, leading to time-saving for medical practitioners. Besides, providing the ranking, instead of just suggesting one or two possible culprit drugs among all prescribed drugs, is expected to help prevent an erroneous identification of culprit drugs.…”
Section: Articlementioning
confidence: 99%
“…This systematic literature review included studies from 1st January 2000 to 16th May 2020. A re‐run of the search was performed in Jan 2022 and two new articles on drug ISB of physicians (Campbell et al, 2021; Jacquot et al, 2020) were found. While the data was not extracted and included in this systematic literature review, the findings are in line with the results of this review.…”
Section: Limitations and Implications For Future Researchmentioning
confidence: 99%